2018
DOI: 10.20473/mog.v24i32016.100-104
|View full text |Cite
|
Sign up to set email alerts
|

Three years survival rate of epithelial ovarian cancer patients in Dr. Kariadi Hospital, Semarang, Central Java

Abstract: Tujuan: mengetahui hubungan antara faktor-faktor prognostik kanker ovarium dengan kesintasan tiga tahun pasien kanker ovarium epitelial. Bahan dan Metode: Penelitian kohort retrospektif pada 90 pasien (selama tahun 2012) di RSUP Dr. Kariadi. Kaplan Meier, Log rank, dan Cox regresi digunakan untuk menganalisa kesintasan dan faktor prognostik yang berhubungan dengan penyakit ini. Hasil: Kesintasan 3 tahun pasien kanker ovarium epitelial secara keseluruhan adalah sebesar 58,5% (Kaplan Meier). Kesintasan 3 tahun p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
(7 reference statements)
0
1
0
1
Order By: Relevance
“…15 The presence of spheroid cells (mesothelial and tumor) in ascites also causes chemoresistance thereby resulting in shorter DFS and OS. [16][17][18][19][20] Tumor conditions with ascites have worse prognoses because they have a much greater potential for metastases. 21 We found that mucinous and clear cell histopathology had a worse survival outcome than those of other histologic types.…”
Section: Discussionmentioning
confidence: 99%
“…15 The presence of spheroid cells (mesothelial and tumor) in ascites also causes chemoresistance thereby resulting in shorter DFS and OS. [16][17][18][19][20] Tumor conditions with ascites have worse prognoses because they have a much greater potential for metastases. 21 We found that mucinous and clear cell histopathology had a worse survival outcome than those of other histologic types.…”
Section: Discussionmentioning
confidence: 99%
“…18 Karsinoma ovarium merupakan kasus yang sulit untuk dilakukan deteksi lebih awal, sehingga angka kematiannya selalu meningkat, sehingga dikenal dengan istilah "the lady silent killer". 19 Kejadian karsinoma ini meningkat karena perubahan gaya hidup terutama di daerah negara berkembang misalnya, nutrisi, merokok, masalah reproduksi. 20 Penelitian ini menunjukkan adanya perbedaan ekspresi CD133 yang bermakna antara karsinoma ovarium derajat rendah dan derajat tinggi (α=0,05; p=0,0001; p<α).…”
Section: Penelitian Yang Dilakukan Ricci Et Al Melaporkan Kasusunclassified